Threshold Concept Pedagogy for Antiracist Social Studies Teaching. (3rd April 2021) - Smith, William L.; Crowley, Ryan M.; Demoiny, Sara B.; Cushing-Leubner, Jenna
Abstract : This conceptual article explores the use of threshold concepts to help pre-service teachers develop antiracist dispositions. Threshold concepts are "troublesome knowledge" within a discipline that serve as gateways to expanded modes of thinking about subject matter. Grappling with threshold concepts places learners in a liminal space as they confront new knowledge that connects them to transformative, irreversible, and integrative understandings. In response to a call for expanding pedagogical content knowledge of threshold concepts in teacher education, we propose the use of threshold concepts as a pedagogical tool to structure methods courses in order to facilitate the growth of PSTs' working racial knowledge. We provide the study of redlining as an exemplar of how to promote the threshold concept of structural racism toward developing PSTs' antiracist dispositions.